2023
DOI: 10.3390/pathogens12020217
|View full text |Cite
|
Sign up to set email alerts
|

Homo- and Heterosubtypic Immunity to Low Pathogenic Avian Influenza Virus Mitigates the Clinical Outcome of Infection with Highly Pathogenic Avian Influenza H5N8 Clade 2.3.4.4.b in Captive Mallards (Anas platyrhynchos)

Abstract: In this study, we investigated the clinical response, viral shedding, transmissibility, pathologic lesions, and tropism of HPAIV Gs/Gd H5N8 subtype (clade 2.3.4.4b), following experimental infection of three groups of captive mallards (Anas platyrhynchos): (i) fully susceptible, (ii) pre-exposed to low pathogenic avian influenza virus (LPAIV) H5N1 subtype, and (iii) pre-exposed to LPAIV H3N8 subtype. Infection of naïve mallards with HPAIV H5N8 resulted in ~60% mortality, neurological signs, abundant shedding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…There were also no large-scale mortalities and few HPAIV detections in sick and dead dabbling ducks, corroborating that these species exhibit less morbidity and mortality compared to other Anseriformes (43). Exposure to LPAIVs has the potential to provide some level of heterosubtypic cross-protective immunity against HPAIV (44). Captive studies have demonstrated that pre-exposure to specific LPAIVs can confer partial cross-protective heterosubtypic immunity to other LPAIVs (4547), as well as HPAIVs (44, 48, 49), which can result in reduced viral loads, duration of shedding, and, in the case of HPAIV, reduced morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were also no large-scale mortalities and few HPAIV detections in sick and dead dabbling ducks, corroborating that these species exhibit less morbidity and mortality compared to other Anseriformes (43). Exposure to LPAIVs has the potential to provide some level of heterosubtypic cross-protective immunity against HPAIV (44). Captive studies have demonstrated that pre-exposure to specific LPAIVs can confer partial cross-protective heterosubtypic immunity to other LPAIVs (4547), as well as HPAIVs (44, 48, 49), which can result in reduced viral loads, duration of shedding, and, in the case of HPAIV, reduced morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Reassortment is a recurring phenomenon among LPAIVs within wild waterfowl populations (64, 65), and H5 subtypes of clades 2.3.4.4 and 2.3.4.4b have demonstrated a high propensity to reassort with LPAIVs (44, 66). The co-circulation of HPAIV and LPAIV among wild bird reservoir species (e.g., dabbling ducks) increases opportunities for mixed infections and the emergence of reassortants (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The H5 clade 2.3.4.4b viruses have exhibited novel epidemiological and pathobiological characteristics distinct from other clades. An elevated pathogenicity has been observed in several duck species [93,94], considered as the AIV natural hosts, accompanied by asymptomatic infections in certain dabbling ducks [95][96][97]. Frequent die-offs have been observed, particularly in colony-breeding seabirds [98][99][100][101], which have been attributed to a shift in the HPAI virus epidemiology among waterbirds, resulting in the endemic circulation of these strains [102,103].…”
Section: H5 Genetic Evolution and Epidemiologymentioning
confidence: 99%
“…For example, as a result of the Mycoplama gallisepticum epizootic in North American House Finches, surviving individuals and populations are resistant to Mycoplasma infection (Bonneaud et al 2019). Studies addressing preexposure of avian influenza have demonstrated that Mallards exposed to LPAI have fewer clinical signs when infected with HPAI compared to those that do not (Tarasiuk et al 2023), which may be a key reason as to why infected Mallards have few disease signs and are able to migrate while infected. Further, long lived species, such as seabirds may retain antibodies for many years, such that both previous LPAI or HPAI infection will be protective (Ramos et al 2014).…”
Section: How To Weather the Storm?mentioning
confidence: 99%